2008
DOI: 10.1080/00016340801934276
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐to‐twin delivery time interval: influencing factors and effect on short‐term outcome of the second twin

Abstract: As twin-to-twin delivery time interval seems to be an independent risk factor for adverse short-term outcome of the second twin, it should be kept short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 20 publications
12
52
2
3
Order By: Relevance
“…In particular, the second twin may have a greater risk of adverse perinatal outcome than the first twin, because of difficulties in delivery due to uterine inertia and abnormal lie or high presentation after the vaginal delivery of the first twin, and increased risk of premature placental separation and cord prolapse 3,4. Although some large-scale epidemiologic studies have reported that there was no difference in the risk of perinatal complications according to birth order 5,6; recent studies have shown that the risk of perinatal mortality and neonatal morbidity was higher in the second twin than the first twin 7,8, and the inter-twin delivery interval have been suggested as an important risk factor associated with the incidence of delivery-related complications in second twins 9.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the second twin may have a greater risk of adverse perinatal outcome than the first twin, because of difficulties in delivery due to uterine inertia and abnormal lie or high presentation after the vaginal delivery of the first twin, and increased risk of premature placental separation and cord prolapse 3,4. Although some large-scale epidemiologic studies have reported that there was no difference in the risk of perinatal complications according to birth order 5,6; recent studies have shown that the risk of perinatal mortality and neonatal morbidity was higher in the second twin than the first twin 7,8, and the inter-twin delivery interval have been suggested as an important risk factor associated with the incidence of delivery-related complications in second twins 9.…”
Section: Introductionmentioning
confidence: 99%
“…Leung et al ont aussi montré, toujours rétrospectivement, à partir de 51 paires de jumeaux, que les pH artériels de J1 et J2 étaient négativement corrélés avec la durée de la deuxième phase de travail, mais que cette détérioration du pH était plus rapide dans le temps lors de la deuxième phase de travail de J2 (définie comme l'intervalle de naissance entre J1 et J2) que lors de celle de J1 (définie comme l'intervalle entre le début des efforts expulsifs et la naissance de J1) [18]. Ces résultats ont été confirmés par deux autres études dont une française [19,20] [21,22]. Cette option active offre l'avantage de réaliser une manoeuvre obstétricale sur un utérus non tonique, à poche des eaux intacte, et a pour objectif de réduire le risque de rétraction du col, de procidence de cordon, de décollement placentaire, et de survenue d'anomalies du RCF sur J2 [21,22].…”
Section: L'accouchement De J2unclassified
“…El intervalo de nacimiento entre gemelos ha sido sugerido como factor de riesgo importante asociado con la incidencia de complicaciones perinatales del segundo nacido (10). En nuestra prác-tica clínica diaria observamos que el pH del cordón del segundo gemelo siempre es igual o menor que el del primero, sobre este hecho postulamos que si el primer gemelo padece un estado acidótico, el estado ácido-base del segundo será igual o más acidótico.…”
Section: Introductionunclassified